Landscape preferences evaluation: Planning of neighborhood parks in Tehran with community-oriented approach - Amir Semiari; Zahra Sadeghi; Fereshteh Rahmani; Farnaz Khaje Saeed (علوم محیطی)
Introduction: Development of a Green Infrastructure and providing per capita and guarantee standards for open spaces in metropolitan areas, must always be foreseen by government in the vision agenda for national development. Especially in Tehran, the importance of green space development has pointed to by the Law of the conservation and development of green spaces and the criteria for comprehensive, detailed and local plans. In addition to the per capita supplement, improvement of open and green spaces through planning and design of neighbourhood parks depends on recognition of popular preferences about landscape. Addressing “landscape preferences” in ecological landscape design is considered to be a key element in the decision-making process. Existing precedents in the literature show that landscape preferences can be divided in three categories, namely the “aesthetic”, “ecological”, and “community-oriented” approaches. In this research, the aim is to evaluate two of the key components - “Activity Pattern” and “Presence Motivation” – of a community-oriented approach in neighbourhood parks that play an important role in developing a landscape planning strategy, according to an environmental psychology approach. Materials and methods: Preferences vary across different communities as they depend on unique contextual factors. As such it is impossible to measure all the factors that affect popular preferences. Data collection in this study was conducted on the basis of a comparative survey under the influence of the underlying “level of welfare” in the Firstand 18th regions of Tehran, which are different in terms of their “welfare”. Using a random sampling method, 363 visitors to neighbourhood parks in regions 1 and 18 participated by filling out our questionnaires, the reliability of which is confirmed. Data analysis was performed using the independent t-test, dependent t-test and ANOVA with the Bonferroni post hoc test within the group in software SPSS. Results and discussion: The results show that the uses of neighbourhood parks in region 1, have a mostly active pattern (p-0/009) while, in region 18, a passive pattern dominates (p-0/002). In region 1, “social factors” of presence motivation in neighbourhood parks have significant differences with “psychological factors” and “environmental and natural factors” (p-0/0001). Active exercises such as walking in outdoors are important for users, who do not consider neighbourhood parks as spaces for social relationships. While, in region 18, neighbourhood parks according to responder attitudes are spaces for resting, being with family and relaxing in natural environments.   Conclusion: The results demonstrate that “the welfare of the people” has a direct impact on the “Activity Pattern” and “Presence Motivation” in the neighbourhood parks. Due to these differences, separate planning strategies for neighbourhood parks in region 1and region 18 must be considered. To motivate people for participating in group activities, in the first region, public sport facilities must be developed. Public participation in the planting and nursing of plants could be implemented and public realms would be increased. In region 18, opportunities for active personal activities with aerobic sports, must be increased to elevate group activities in the park. Also, planners and designers must pay attention to variety of people’s needs for green infrastructures. The inclusive landscape design approach is an advantageous strategy for responding to the variable needs of visitors, especially in the neighbourhood parks of region 18. This research highlights the merit of surveying and evaluating “landscape preferences” as a preliminary step in the authorship of planning strategies. This approach provides a guideline for the recognition of design generators of neighbourhood parks, based on environmental psychology and community-oriented norms.